(untitled) (Research, Society and Development, 2021)
Orthopedic conditions are quite common in animal veterinary medicine, which can be highlighted as fractures. The objective of this study was to verify the prevalence of fractures in the animals treated at the University Veterinary Hospital (HVU) of the Federal University of Vale do São Francisco (UNIVASF) by the Animal Surgery Clinic of the Company (CCAC) in an extension project of specialized care in surgical clnic and from this survey, fractures the most affected animals, the influence of infants on fractures and the most common causes of fractures. For an evaluation of this study, it was necessary to have access to the medical records and radiography of the University Veterinary Hospital of UNIVASF, which included data from 2016 to 2018, totaling 55 cases of fractures, mainly in medical records and 87% of dogs. These fractures are quite common in HVU - UNIVASF due to high numbers of wrong animals and the lack of care and guidance of some tutors in the City of Petrolina - Pernambuco.